2023
DOI: 10.3390/biom13020214
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNAs in Ischemic Stroke: Biological Role and Experimental Models

Abstract: Ischemic stroke is among the leading causes of morbidity, disability, and mortality worldwide. Despite the recent progress in the management of acute ischemic stroke, timely intervention still represents a challenge. Hence, strategies to counteract ischemic brain injury during and around the acute event are still lacking, also due to the limited knowledge of the underlying mechanisms. Despite the increasing understanding of the complex pathophysiology underlying ischemic brain injury, some relevant pieces of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…For example, stimulation of serum-exos by oxidized low-density lipoprotein (oxLDL), hyperglycemia or hypertension, which are established risk factors for atherosclerotic vulnerable plaques, can lead to the upregulation of inflammation-and proliferationrelated genes within exosomes and exert corresponding functional effects [10][11][12][13] . Notably, previous research and our sequencing analysis revealed that suppression of SMC phenotypic switching-related genetic content was most significantly increased in serum-exos from patients with stable plaques (SPs) compared to those from patients with vulnerable plaques [14][15][16][17] , suggesting that the principal function of serum exosomes containing pertinent genetic content from SPs might be to regulate SMC phenotypic switching. Serum-exos are characterized by biocompatibility, low immunogenicity, and minimal adverse reactions 18,19 .…”
Section: Introductionmentioning
confidence: 86%
“…For example, stimulation of serum-exos by oxidized low-density lipoprotein (oxLDL), hyperglycemia or hypertension, which are established risk factors for atherosclerotic vulnerable plaques, can lead to the upregulation of inflammation-and proliferationrelated genes within exosomes and exert corresponding functional effects [10][11][12][13] . Notably, previous research and our sequencing analysis revealed that suppression of SMC phenotypic switching-related genetic content was most significantly increased in serum-exos from patients with stable plaques (SPs) compared to those from patients with vulnerable plaques [14][15][16][17] , suggesting that the principal function of serum exosomes containing pertinent genetic content from SPs might be to regulate SMC phenotypic switching. Serum-exos are characterized by biocompatibility, low immunogenicity, and minimal adverse reactions 18,19 .…”
Section: Introductionmentioning
confidence: 86%
“…They are involved in the pathophysiological processes underlying ischemic stroke, and emerging evidence points to their potential as therapeutic targets and clinical biomarkers. 26 Indeed, in EVs derived from preconditioned sources, the researchers found an enhanced expression of the specific circRNA, circ-Rps5. They further elucidated the mechanistic pathway by which circ-Rps5 acts through downstream effects on SIRT7 and miR-124-3p, thereby modulating the shift in microglial phenotype.…”
Section: Concepts Of Ev Preconditioningmentioning
confidence: 99%
“…Current diagnosis for IS is mainly based on the use of computed tomography scan or magnetic resonance imaging after the patient is hospitalized 2 . In the past decade, studies have emerged suggesting other potential diagnostic approaches for different diseases including the dysregulation of microRNAs (miRNAs) and circular RNAs 3 . miRNAs have become one of the most promising types of biomarkers among these approaches and were extensively studied for their potential use in cancers, nervous system disorders and cardiovascular diseases 4 .…”
Section: Introductionmentioning
confidence: 99%